A Descriptive Study to Assess the Knowledge on Fetal Well Being among Antenatal Mothers with Selected Tertiary Care Hospital at Kelambakkam, Kanchipuram District, Tamil Nadu, India (Medico Legal Update, 2020)
Objectives: To assess the knowledge on fetal well being among antenatal mothers in selected tertiary carehospital at Kelambakkam, Kanchipuram District, Tamil Nadu.Methodology: Thenon probability purposive sampling technique sampling technique with the sample of 45antenatal mothers and questionnaires were formulated structured questionnaire schedule were used to assessthe knowledge.Results: Majority of antenatal mothers are inadequate knowledge about fetal well being.Conclusion: The study was conclude improve the knowledge on antenatal mothers about fetal well being.